Teaching of ethics in public administration courses: An analysis from Pedagogical Projects of Course and the National Curricular Guidelines - Laís Silveira Santos; Mauricio C. Serafim; Marcello Beckert Zappellini; Silvia Maria Knabben Corrêa Zappellini; Martha Kaschny Borges (Arizona State University, 2018)
The National Curricular Guidelines (DCN) of the undergraduate program in Public Administration bring the discussion and the teaching of ethics as a basic and indispensable disciplinary content to the education of the student. From this finding, the interest in knowing how its teaching occurs and assists the professional education of undergraduate students in Public Administration in Brazil emerged. For that, we developed a document research in the Pedagogical Projects of Courses (PPC) of the Public Field. Based on selection criteria, 15 PPC were included in the study. The undergraduate programs of the Public Field, guided by the republican and democratic ethos, should reproduce this fundamental principle in all teaching-learning processes and this was observed when analyzing the PPC, through the analysis categories of the curricular matrix, syllabuses of the courses and graduate profile. We verified that in most projects there is a search for the insertion of the discussion of ethical, critical and reflexive action both during the program and in the professional practice. Regarding ethics teaching, we believe that as the theme gains strength in the analysis of organizations, it might lead administrators to develop/adopt a more reflexive, critical and socially responsible position.